461PBlood trace minerals and lung cancer: A Mendelian randomization study. (24th November 2019) - Xian, W; Zhou, H; Zhang, Y; Shen, J; Liu, J; Zhang, L
Abstract: Background: Meta-analyses and cohort studies have shown blood trace mineral concentration may be associated with incidence risk of lung cancer. However, there is no comprehensive study to investigate causal relationship between blood trace mineral and lung cancer. The purpose of this study is to inspect the causal effect of blood trace mineral concentration on lung cancer with Mendelian randomization (MR) method. Methods: With a two‐sample MR approach, we analyzed the summary data of zinc, selenium, copper from the Queensland Institute of Medical Research(QIMR, 2603 individuals) and The Avon Longitudinal Study of Parents and Children (ALSPAC, 10115 individuals), data of calcium from discovery cohorts(39400 individuals) and replication cohorts(21875 individuals), data of iron from Genetics of Iron Status Consortium(23986 individuals), data of lung cancer patients from Consortium and International Lung Cancer Consortium (ILCCO, 11 348 lung cancer cases and 15 861 controls) to assess the possible causal relationship of blood trace mineral concentration on the risk of lung cancer. Results: Our results indicated that genetically predicted higher blood copper level has a positive association with lung cancer, each per-unit increase in copper is associated with a 14% increase in the risk of lung cancer (odds ratio [OR]: 1.14, 95% CI = 1.01‐1.29; P = 0.04). Additionally, blood calcium, zinc, selenium, iron were not causal factors for lung cancer. Conclusions: Genetically higher blood copper is positively associated with risk of lung cancer, and more work is needed to examine the potential mechanism. Legal entity responsible for the study: The authors. Funding: National Key R&D Program of China (Grant No. 2016YFC0905500, 2016YFC0905503); Science and Technology Program of Guangdong (Grant No. 2017B020227001, 2016A020215084); Science and Technology Program of Guangzhou (Grant No. 201607020031, 201400000001-2); Chinese National Natural Science Foundation project (Grant No. 81772476, 81572659, 81602011); Pearl River Nova Program of Guangzhou (Grant No. 201610010048); National Natural Science Funds for Young Scholars of China (Grant No. 81502355). Disclosure: All authors have declared no conflicts of interest.